Cytochrome P450 endoplasmic reticulum-associated degradation (ERAD): therapeutic and pathophysiological implications - Doyoung Kwon; Sung-Mi Kim; Maria Almira Correia (Elsevier, 2020)
The hepatic endoplasmic reticulum (ER)-anchored cytochromes P450 (P450s) are mixed-function oxidases engaged in the biotransformation of physiologically relevant endobiotics as well as of myriad xenobiotics of therapeutic and environmental relevance. P450 ER-content and hence function is regulated by their coordinated hemoprotein syntheses and proteolytic turnover. Such P450 proteolytic turnover occurs through a process known as ER-associated degradation (ERAD) that involves ubiquitin-dependent proteasomal degradation (UPD) and/or autophagic-lysosomal degradation (ALD). Herein, on the basis of available literature reports and our own recent findings of in vitro as well as in vivo experimental studies, we discuss the therapeutic and pathophysiological implications of altered P450 ERAD and its plausible clinical relevance. We specifically (i) describe the P450 ERAD-machinery and how it may be repurposed for the generation of antigenic P450 peptides involved in P450 autoantibody pathogenesis in drug-induced acute hypersensitivity reactions and liver injury, or viral hepatitis; (ii) discuss the relevance of accelerated or disrupted P450-ERAD to the pharmacological and/or toxicological effects of clinically relevant P450 drug substrates; and (iii) detail the pathophysiological consequences of disrupted P450 ERAD, contributing to non-alcoholic fatty liver disease (NAFLD)/non-alcoholic steatohepatitis (NASH) under certain synergistic cellular conditions. Key words: Cytochromes P450, Endoplasmic reticulum-associated degradation, CHIP E3 ubiquitin ligase, gp78/AMFR E3 ubiquitin ligase, JNK1, AMPK1, Non-alcoholic fatty liver disease, Non-alcoholic steatohepatitis